Teacher Challenges In Teaching Slow Learners - Ariyanti, Sefti Dwi; Putra, Satria Dwi; Zuhria, Fatimmatuz; Rahayu Sulistiyawati, Dhesta Youlandi (ALENA : Journal of Elementary Education, 2025)
Teaching students with special needs, such as slow learners, is a major challenge in implementing inclusive education. Slow learners require a more focused and flexible learning approach to support their understanding of the material being taught. In primary schools, such as SD Negeri 2 Kalipetir, inclusive education plays a key role in ensuring that all students, including those with learning difficulties, can reach their full potential. The purpose of this study is to identify the approaches and strategies applied by teachers in teaching slow learner students in class V of SD Negeri 2 Kalipetir, assess the barriers faced, as well as the impact on student development. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The research findings show that teachers use various strategies, such as adjusting learning materials, utilizing interactive media, and collaborating with parents. Despite limitations in terms of time and facilities, this approach proved effective in improving the understanding of material and social skills of slow learner students. This research makes an important contribution to the development of more effective inclusive learning strategies at the primary school level.